Pembaca Sebagai Penikmat Karya Sastra: Menguak Topik Teratas Fiksimini di Twitter: Readers as works of literature: revealing the top flash fiction topics on Twitter - Sari, Arini Vika (Himpunan Sarjana Kesusastraan Indonesia (HISKI) Komisariat Kalimantan Timur, 2023)
This study aims to describe the most popular flash fiction topics by readers and connoisseurs of flash fiction literary works on Twitter. This descriptive qualitative research uses data sources from the @fiksimini Twitter account from July 2019 to July 2020. The reading and note-taking technique were used for data collection, with the data collection instrument being the researcher who used the parameters of Iser's literary reception theory. Data analysis was conducted through three stages: data reduction, data presentation, and conclusion drawing. The results showed that the topics presented by the @fiksimini account can be divided into three issues: past, current, and future. The issue of the future is the top topic and is most in demand by readers and literature lovers, with an average score of 9.38. In addition, readers and viewers of the @fiksimini account can contribute to creating interesting flash fiction stories. The digital literary activity occurs due to the reception of readers involved in creating flash fiction by 65.21% and readers' retweets of flash fiction topics by 2.1%. Readers who can enjoy and contribute to digital literature on the @fiksimini Twitter account can make this digital literature work increasingly popular among the public.